Element the good practice in reviving and preserving the value of MTCs / Zainudin Md Nor ... [et. al] - Zainudin, Md Nor; Zaharah, Jaafar; Muhamad Rozali, Othman; Rizal Azni, Dahaman (Universiti Teknologi MARA, Perak, 2018)
The purpose of this study is to identify the values of the Malay Traditional Costume (MTCs) which have always been said by researches and local cultural as being eroded by the effect of modernization. This research justifies factors that contribute the best practises to revive the values of MTCs in Malaysia. A quantitative and qualitative method was used to conduct the research. The study involves questionnaire survey and interviews. Direct and indirect questions were used as an interview method. The researcher has interviewed 60 respondents who are experienced and expert in their field of the making and styling of the traditional Malay costume; such as old tailors and old dressmakers, fashion designers, industrialist, choreographers, culturalist, researchers and lecturers. The questionnaires were also forwarded to 26 teachers and 380 secondary school students Perak, Kedah, Penang and Perlis states. A small group of the respondents were chosen as a case study as they were able to produce, maintain and restore the traditional Malay costume. The findings showed that there were a significance relationship among five component values for future development and ustainability in the MTCs which are cultural and heritage values, educational values, art and aesthetic values, design and functional values and lastly socio economic values. As a conclusion there were 4 elements they can play a major role in reviving and preserving the value of MTCs; the teaching and learning of MTCs in higher institutes of learning, the involvement of royal families, NGO’s and activists. Thirdly is the involvement of local fashion designers, fashion entrepreneur and government agencies. The final factor is the best technique to appreciate MTC as a national culture. This research recommended that integration among these groups are factors that contribute to the creation of model of good practice for future development of Malay traditional costume in Malaysia.